Public policy: a new introduction - Knill, Christoph; Tosun, Jale (Textbooks in policy studies, 2020)
A comprehensive introduction to public policy and the policy cycle, the fully revised second edition of this popular textbook offers a practical guide to the topic while remaining underpinned by cutting-edge research. Bringing together analysis of classic works alongside the most recent developments in the field, this book is guided by the following three crucial questions: What is public policy? Who participates in making and putting public policy in practice as well as in assessing its success? And when and how does public policy change over time? In answering these questions, the book covers everything from the central institutions and actors of policy-making to implementation, evaluation and governance. Drawing on examples from across the world, the new edition expands on themes that were previously covered only marginally, including the underexplored connection between public policy and political economy, as well as placing more emphasis on climate change and practical advice on doing policy analysis. For undergraduate or postgraduate students studying on courses focussed on public policy or the policy cycle or process, this textbook is the essential guide to the subject. The book is also suited for those studying public policy in the context of politics or public management and administration. --